Hunger strikes in prison: a legal perspective for psychiatrists. (25th October 2017) - Gulati, G.; Whelan, D.; Spain, E.; Meagher, D.; Dunne, C. P.
Abstract : Hunger strikes in a custodial setting are complex to manage clinically, with associated legal and ethical complexities. Hunger strikes in Irish prisons have received, and are likely to continue to be the focus of, considerable media attention. Whilst there is an internationally accepted consensus ethical position, there is limited legal guidance available for psychiatrists to draw upon in such cases. In this paper, we review recent case-law and discuss the legal considerations in the management of prisoners on hunger strike.